Pengembangan Permainan Sevolbas Dengan Pendekatan Pembelajaran Integrated Untuk Pembelajaran Bola Besar Penjasorkes Sekolah Dasar - Julianur Julianur; Muhammad Sukron Fauzi; Sukriadi Sukriadi (Universitas PGRI Semarang, 2020)
Sevolbas Game Development With Integrated Learning For Large Ball In Physical Education Elementary SchoolThe purpose of this research is to produce a product for the development of large soccer balls, volleyball and basketball (Sevolbas) as a medium for teaching physical education for elementary school students. The research method used is R&D. The development procedure includes several stages: analyzing the product, developing, initial product play, expert validity, small group testing, product revision, large-scale trial, product revision, and product development results. The instruments used were interviews, observations, questionnaires, and documentation. Subjects and research sites were elementary school students in Samarinda City, SDN 008, SDN 002 and SD Muhammadiyah 1 with a total of 103 research subjects. The analysis technique used is the feasibility, product quality and product acceptance. The results obtained for the activeness of student movements have increased 52.25% and have reached 80% of the maximum maximum pulse rate of 91.54. For the quality of the model, facilities and infrastructure show that 60% in the category is very good. For the interest or interest of students in the game activities as wide as 59% showed high student interest. Whereas for the three high cognitive domains, and the psychomotor category is medium and the affective domain is in the medium category. The conclusion from the results of this study is that the product of sevolbas game activities for the learning of the big ball of elementary school physical education is feasible and can be accepted or used in the physical education lesson of the elementary school big ball learning material.Keywords: Sevolbas game, integrated learning approach Tujuan penelitian ini adalah menghasilkan produk pengembangan bola besar sepak bola, bola voli dan bola basket (Sevolbas) sebagai media pengajaran penjasorkes bagi siswa sekolah dasar. Metode penelitian yang digunakan adalah R&D. Prosedur pengembangan meliputi beberapa tahap: menganalisis produk, mengembangkan, produk awal permainan, validitas ahli, uji kelompok kecil, revisi produk, uji coba skala besar, revisi produk, dan hasil produk pengembangan. Instrument yang digunakan wawancara, observasi, kuesioner, dan dokumentasi. Subjek dan tempat penelitian adalah siswa Sekolah Dasar di Kota Samarinda SDN 008, SDN 002 dan SD Muhammadiyah 1 dengan jumlah subjek penelitian 103 siswa. Teknik analisis yang digunakan adalah kelayakan, kualitas produk dan keterimaan produk. Hasil penelitian yang diperoleh untuk keaktifan gerak siswa mengalami peningkatan 52,25% dan telah mencapai 80% dari denyut nadi maksimal rata-rata 91,54. Untuk kualitas model, sarana dan prasarana menunjukan bahwa 60% dalam katagori sangat baik. Untuk minat atau ketertarikan siswa terhadap aktivitas permainan sevolbas menunjukan 59% minat siswa yang tinggi. Sedangkan untuk ketiga ranah kognitif tinggi, dan psikomotorik katagori sedang dan ranah afektif dalam katagori sedang. Kesimpulan dari hasil penelitian ini yaitu produk aktivitas permainan sevolbas untuk pembelajaran bola besar penjasorkes sekolah dasar layak dan dapat diterima atau digunakan dalam pelajaran penjasorkes materi pembelajaran bola besar sekolah dasar.Kata kunci: Permainan sevolbas, pendekatan integrated learning